2014
DOI: 10.1063/1.4892875
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Nanoscale ion fluctuations in Nafion polymer electrolyte

Abstract: Ion conduction mechanisms and the nanostructure of ion conduction networks remain poorly understood in polymer electrolytes which are used as proton-exchange-membranes (PEM) in fuel cell applications. Here we study nanoscale surface-potential fluctuations produced by Brownian ion dynamics in thin films of low-hydration Nafion™, the prototype PEM. Images and power spectra of the fluctuations are used to derive the local conductivity-relaxation spectrum, in order to compare with bulk behavior and hopping-conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 32 publications
6
8
0
Order By: Relevance
“…Furthermore, the extent of variation in lifetimes upon decrease in hydration level is less in annealed film than in nonannealed films. This is in agreement with a report in which annealing was found to generate completely dried regions having a crystalline fluorocarbon backbone that is difficult to hydrate . This makes water uptake of annealed films difficult.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the extent of variation in lifetimes upon decrease in hydration level is less in annealed film than in nonannealed films. This is in agreement with a report in which annealing was found to generate completely dried regions having a crystalline fluorocarbon backbone that is difficult to hydrate . This makes water uptake of annealed films difficult.…”
Section: Resultssupporting
confidence: 92%
“…Previous dielectric spectroscopy studies reported that Nafion membranes exhibits two distinct dc conduction processes, one occurring at high frequencies ( f ∼ 10 6 Hz) and another at lower frequencies ( f < 10 −1 Hz) . Evidences of two dc conductivities have been also provided by different techniques, such as electric force microscopy (EFM), NMR, quasielastic neutron scattering, and radiotracer studies of Nafion membranes . Such reports revealed ion conduction process occurring at long time scales t ∼ 1 – 100 s ( f ∼ 10 0 – 10 −2 Hz), in agreement with the low‐frequency data of Figure .…”
Section: Resultssupporting
confidence: 78%
“…The depth of the contrasted regions is~5 nm in agreement with previous AFM analysis [16,30]. In these images, the topography displays a rather irregular structure.…”
Section: Afmsupporting
confidence: 85%
“…The crossover frequency from ac to dc conductivity, identified in earlier reports at f~10 À3 Hz [17], is in good agreement with the onset frequency for dc conductivity, observed at f < 10 À3 Hz [15,17,19]. Therefore, the relaxation observed at f~10 À3 Hz in Nafion dielectric spectrum can be attributed to a conductive dispersion (s relaxation) [16,21]. Fig.…”
Section: Identification Of the A-relaxationsupporting
confidence: 81%
See 1 more Smart Citation